ARTIST‐TEACHER PARTNERSHIPS IN LEARNING: THE IN/BETWEEN SPACES OF ARTIST‐TEACHER PROFESSIONAL DEVELOPMENT - Kind, Sylvia; de Cosson, Alex; Irwin, Rita; Grauer, Kit (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
Artist‐in‐residence programs frequently act as professional development initiatives for teachers. Little understanding of the relational nature of artist‐teacher learning exists. In this article, we discuss Learning Through The Arts TM, describing conflicting expectations as artists and teachers learn from each other, and explore the relationship of artists’ growth and learning to teacher development. Using participants’ narratives, we illustrate existing tensions and challenges for visual art education. We present the need to open spaces for artists to construct new understandings of themselves as teachers in relation to themselves as artists, and for teachers to develop artist selves alongside their teacher selves. Key words: teacher learning, artists as teachers, artists in schools, relational learning, educational dilemmas, beliefs, Learning Through The ArtsTM Les programmes d’artistes en résidence font souvent office d’initiatives de perfectionnement professionnel pour les enseignants. On a peu exploré la nature de la relation entre l’apprentissage de l’artiste et celui de l’enseignant. Dans cet article, les auteurs discutent du programme Apprendre par les artsMC ; ils décrivent les attentes conflictuelles des artistes et des enseignants et explorent le lien entre l’évolution et l’apprentissage de l’artiste et le perfectionnement professionnel de l’enseignant. À l’aide des comptes rendus des participants, ils illustrent les tensions et les défis inhérents à l’enseignement des arts visuels. Ils décrivent le besoin de créer un espace permettant aux artistes de se comprendre eux‐mêmes comme enseignants dans leurs rapports avec leur identité d’artistes et aux enseignants de se développer comme artistes en même temps que comme enseignants. Mots clés : apprentissage chez les enseignants, artistes‐enseignants, artistes à l’école, apprentissage relationnel, dilemmes pédagogiques, croyances, Apprendre par les arts